The Spiritual Dimension in Film: The Existence of Images in Film as Human Life according to Gilles Deluez - Ai Ahmad Faisal (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2022)
The purpose of this article is to discuss the nature of images in films according to Gilles Deleuze. Film according to Deleuze consists of images and motion. Image and motion are related and complementary. When humans watch a film, the human mind through the five senses perceives a series of moving images. The finding of this article is that Deleuze views films from ontological and spiritual dimensions. The ontological dimension of film philosophy is that images that move and have duration in the film are real everyday life so that there is no distance between the audience and what is being watched in the film. The ontological aspect of Deleuze's film philosophy is continuous becoming and the essence that precedes existence. While the spiritual dimension in film is an image that moves continuously which is an expression of the senses and human reason. These moving images have a soul or spirit that makes the audience drift into a film's life story. This study uses an analytical descriptive approach. By using analytical descriptive it is produced that the picture in the film is an artificial existence of human life. The existence of imitation human life in films becomes independent from the existence of human life in external reality because it has a different time and the duration has been determined by the humans themselves.